Penerapan Teknik Stress Inoculation Training (SIT) untuk Mereduksi Post Traumatic Stress Disorder (PTSD) pada Remaja Korban Kekerasaan Seksual (Studi Kasus Klien “R”) - Dari, Ayu Fitria Wulan; Razzaq, Abdur; Noviza, Neni (Journal of Society Counseling, 2023)
This study analyzes the Application of Stress Inoculation Training (SIT) Techniques to Reduce Post Traumatic Stress Disorder (PTSD) in Adolescent Victims of Sexual Violence (Case Study of Client "R" in Betung OKUT Village). The aim of the study was to find out the symptoms of post traumatic stress disorder (PTSD) in young victims of sexual violence experienced by client "R", to find out the stress inoculation training (SIT) approach to reduce post traumatic stress disorder (PTSD) in young victims of sexual violence. Data collection techniques through observation, interviews and documentation. The results showed: 1) The characteristics of post traumatic stress disorder in the client "R" are currently quite apprehensive, often feeling afraid of meeting other people or just remembering the shadows of the bitter event, then the client experiences anxiety, anxiety which makes it difficult to control emotions so that the client I have trouble sleeping because I often have nightmares. 2) Application of the stress inoculation training (SIT) technique to client "R" based on the results of research on the application of the stress inoculation training (SIT) technique through 6 meetings using 3 stages namely the initial stage, the middle stage (work stage) and the final stage. With 6 meetings it can be concluded that in reducing post traumatic stress disorder (PTSD) experienced by client "R" there were several changes felt by client "R" after carrying out the application the client "R experienced calm and increased confidence already willing to interact with people others, more enthusiastic in living life and always strong and patient in facing the problems that will be faced in the future.